The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5152/tao.2015.1351
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Otorhinolaryngology Residents about Their Education Process

Abstract: Objective: Our study was planned to get the views of residents about the Otorhinolaryngology (ORL) education process and to enlighten the studies to make this process more effective. Methods:A questionnaire was sent to the residents who were still in the residency program in all education clinics via "Google Drive". Seventy-four of 354 residents responded and the answers were evaluated electronically.Results: Fifty residents (67.56%) gave an affirmative answer to the question about the use of "Resident Log Boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…As in all the surgical branches, also the ENT residency is a tiring and challenging process for the residents ( 13 ). Despite this fact, the results of the present study suggest that 89% of ENT residents wanted to participate in scientific research activities during their residency period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in all the surgical branches, also the ENT residency is a tiring and challenging process for the residents ( 13 ). Despite this fact, the results of the present study suggest that 89% of ENT residents wanted to participate in scientific research activities during their residency period.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, it was reported that, although residents might want to participate in scientific research projects, they may sometimes face several obstacles such as lack of knowledge-skill, insufficient time, and lack of financial support ( 14 , 21 ). The surgical residency educations incorporate an intense study program ( 13 ). For this reason, no time can be allocated to scientific research projects and educations while running routine healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Türkiye'de acil tıp uzmanlık eğitiminin değerlendirildiği bir anket çalışmasında ise (22), dahil edilen 20 bölümün 16'sında (%80) asistan el kitabı kullanıldığı saptanmıştır. Kulak burun boğaz hastalıkları asistanlarını içeren daha yeni bir anket çalışmasında ise bu oran %67 olarak verilmektedir (23). Ancak mevcut durumda, sorunun eğitim programı veya asistan el kitabı yokluğundan çok etkin kullanıma dair yetersizlik ve isteksizlik ile bunların yapılandırma ve uygulama süreçlerinin şeffaflığındaki eksiklikler olduğu düşünülebilir.…”
Section: Mevcutunclassified
“…Cerrahi dallarda sosyal desteğin fiziksel boyutu daha da önemli olabilir. Türkiye'de kulak burun boğaz hastalıkları uzmanlık öğrencilerin %89'u eğitim sürecini "yorucu" ve %70'i "stresli" olarak tanımlamaktadır (23). Cerrahi asistanlarının hastane nöbetlerindeki aktivitelerinin diğer bir "gölge asistan" tarafından değerlendirilmesine dayanan bir çalışmada, nöbet süresinin sadece %30'unun hasta değerlendirme ile geçtiği; geri kalan zamanın ise uyku gibi günlük aktivitelere (%35) ek olarak dosya hazırlama, iletişim ve tanısal değerlendirme gibi diğer işlere ayrıldığı saptanmıştır (24).…”
Section: Mevcutunclassified
“…Although the sources for surgical training are currently diversified with educational videos, simulations, cadaver studies, and clinical skills laboratories, the basis of surgical training is still the master-apprentice relationship. This model of the master-apprentice relationship, which is accepted to be the basic approach to surgical training, was firstly defined by Halsted and Osler in literature (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%